Impact of Globalization and Liberalization on Jewellery Artisans: A Diagnostic Study - Achar, Ananthapadhmanabha (Prabandhan: Indian Journal of Management, 2012)
Artisan dependent jewellery business in India has an unbroken heritage of over 5,000 years and remained a traditional art work. Jewellery making - goldsmithery was a hereditary profession in India, which has been mainly practiced by a particular community called the 'Vishwakarma' community. Until recently, only the traditional goldsmiths of the Hindu Vishwakarma Community were engaged in gold jewellery making at their house-cum workshop. Today, this sector has attracted workers from other industries due to competitive advantage/high rate of return on investment. Due to this, traditional jewellery artisans, who had made a significant contribution to the growth of art and culture of jewellery making, are now facing the problems of underemployment, unemployment, low earnings and an uncertain future. Small family goldsmith units are dwindling. Notwithstanding this, there are about 5000 artisans in the Mangalore region with a high level of skills in the area of traditional jewellery designing that can cater to a niche market where they have a competitive advantage over the corporates and large manufacturers. Assisting these artisans to apply their unique skills to tap the potential market through a cluster approach may lead to considerable economic benefits directly for the goldsmiths and spill over benefits for entrepreneurs on the supply side. In this context, a diagnostic study of the Gold Jewellery Cluster in Mangalore was carried out to assess the impact of globalization and liberalization on the jewellery artisans in Mangalore. The study reveals that the goldsmiths are facing the problems of (1) Lack of technical expertise (2) Excessive dependence on the traders for marketing (3) No access to formal training (4) Limited access to Institutional Finance (5) Absence of a common facility centre.